IDENTIFIYING THE BANKRUPTCY RISK OF COMPANIES WITH THE ALMAN MODEL - GROSU, Veronica; MACSIM, Ancuta Roxana (Ecoforum Journal, 2019)
Companies operate to produce goods and services that, in turn, help the entity achieve its primary objective of gaining profits. Certain studies have been conducted to determine whether an economic entity is sound and capable of continuing its business in a normal way. There are a lot of papers in which this topic is debated, and these are proposed by different specialists. Altman is one of these authors. It has developed a model based on the financial statements of economic entities. With the help of this report, Altman could predict about 2-3 years in advance whether an economic entity is financially efficient or whether it will be on the verge of bankruptcy.